2017
DOI: 10.1210/jc.2016-3529
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid Cancer Following Childhood Low-Dose Radiation Exposure: A Pooled Analysis of Nine Cohorts

Abstract: Context:The increased use of diagnostic and therapeutic procedures that involve radiation raises concerns about radiation effects, particularly in children and the radiosensitive thyroid gland.Objectives:Evaluation of relative risk (RR) trends for thyroid radiation doses <0.2 gray (Gy); evidence of a threshold dose; and possible modifiers of the dose-response, e.g., sex, age at exposure, time since exposure.Design and Setting:Pooled data from nine cohort studies of childhood external radiation exposure and thy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
93
0
9

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 131 publications
(104 citation statements)
references
References 44 publications
2
93
0
9
Order By: Relevance
“…internal exposure. Both cohorts showed linear dose-response functions with little evidence of nonlinearity [45][46][47], though with an apparently lower risk per unit dose than seen in studies of children exposed to external radiation at fairly high dose rates [48]. The estimated thyroid doses are reasonably accurate though still uncertain [49], which lends support to a LNT interpretation following childhood exposures.…”
Section: Environmental Exposure Studiesmentioning
confidence: 60%
See 2 more Smart Citations
“…internal exposure. Both cohorts showed linear dose-response functions with little evidence of nonlinearity [45][46][47], though with an apparently lower risk per unit dose than seen in studies of children exposed to external radiation at fairly high dose rates [48]. The estimated thyroid doses are reasonably accurate though still uncertain [49], which lends support to a LNT interpretation following childhood exposures.…”
Section: Environmental Exposure Studiesmentioning
confidence: 60%
“…Conducting pooled studies [13] and meta-analyses [6,72,73] Although several studies showed null/negative dose-response relations for solid cancer (Table 1) or provided only limited evidence of a positive association at doses under about 100 mGy [32,43], a variety of studies has shown elevated solid cancer occurrence in the low-dose range [6,10,13,25,48]. Eleven (38%) studies provided moderate or strong support for the LNT model for radiation protection (Table 1), and other LD/LDR reports indicate dose-related elevations in leukemia risk [14,26,44,[81][82][83].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The fifth study is the pooled analysis of thyroid cancer incidence after childhood radiation exposures (58). One issue with this study is that thyroid cancer incidence is subject to considerable overdiagnosis.…”
Section: Discussion Of Ncrp Commentary 27mentioning
confidence: 99%
“…Children who have been exposed to radiation therapy (13)(14)(15) or chemotherapy (15) have an increased risk of developing thyroid nodules and thyroid cancer, as do patients with certain tumor predisposition syndromes, such as phosphatase and tensin hamartoma tumor and familial adenomatous polyposis syndromes (1). Although the American Thyroid Association does not currently recommend screening US of the thyroid in children in high-risk categories, it does recommend annual physical examination of the gland in these children (1).…”
mentioning
confidence: 99%